Exploration and development of PPAR modulators in health and disease : an update of clinical evidence - Cheng, Hong Sheng (2020)
Peroxisome proliferator-activated receptors (PPARs) are nuclear receptors that govern the expression of genes responsible for energy metabolism, cellular development, and differentiation. Their crucial biological roles dictate the significance of PPAR-targeting synthetic ligands in medical research and drug discovery. Clinical implications of PPAR agonists span across a wide range of health conditions, including metabolic diseases, chronic inflammatory diseases, infections, autoimmune diseases, neurological and psychiatric disorders, and malignancies. In this review we aim to consolidate existing clinical evidence of PPAR modulators, highlighting their clinical prospects and challenges. Findings from clinical trials revealed that different agonists of the same PPAR subtype could present different safety profiles and clinical outcomes in a disease-dependent manner. Pemafibrate, due to its high selectivity, is likely to replace other PPARα agonists for dyslipidemia and cardiovascular diseases. PPARγ agonist pioglitazone showed tremendous promises in many non-metabolic disorders like chronic kidney disease, depression, inflammation, and autoimmune diseases. The clinical niche of PPARβ/δ agonists is less well-explored. Interestingly, dual- or pan-PPAR agonists, namely chiglitazar, saroglitazar, elafibranor, and lanifibranor, are gaining momentum with their optimistic outcomes in many diseases including type 2 diabetes, dyslipidemia, non-alcoholic fatty liver disease, and primary biliary cholangitis. Notably, the preclinical and clinical development for PPAR antagonists remains unacceptably deficient. We anticipate the future design of better PPAR modulators with minimal off-target effects, high selectivity, superior bioavailability, and pharmacokinetics. This will open new possibilities for PPAR ligands in medicine.